Ore Genesis and Tectonic Significance of the Xiaojiashan Tungsten Deposit, Eastern Tianshan, Xinjiang, China: Evidence from Geology, Fluid Inclusions, and Stable Isotope Geochemistry. Issue 1 (13th August 2018) - Zhou, Yunfei; Xu, Jiuhua; Shan, Lihua; Cheng, Xihui; Deng, Yueping; Feng, Wenhuan; Qiao, Lingxiao
Abstract: The Xiaojiashan tungsten deposit is located about 200 km northwest of Hami City, the Eastern Tianshan orogenic belt, Xinjiang, northwestern China, and is a quartz vein‐type tungsten deposit. Combined fluid inclusion microthermometry, host rock geochemistry, and H–O isotopic compositions are used to constrain the ore genesis and tectonic setting of the Xiaojiashan tungsten deposit. The orebodies occur in granite intrusions adjacent to the metamorphic crystal tuff, which consists of the second lithological section of the first Sub‐Formation of the Dananhu Formation (D2 d 1 2 ). Biotite granite is the most widely distributed intrusive bodies in the Xiaojiashan tungsten deposit. Altered diorite and metamorphic crystal tuff are the main surrounding rocks. The granite belongs to peraluminous A‐type granite with high potassic calc‐alkaline series, and all rocks show light Rare Earth Element (REE)‐enriched patterns. The trace element characters suggest that crystallization differentiation might even occur in the diagenetic process. The granite belongs to postcollisional extension granite, and the rocks formed in an extensional tectonic environment, which might result from magma activity in such an extensional tectonic environment. Tungsten‐bearing quartz veins are divided into gray quartz vein and white quartz veins. Based on petrography observation, fluid inclusions in both kinds of vein quartz are mainly aqueous inclusions. Microthermometry shows that gray quartz veins have 143–354°C of T h, and white quartz veins have 154–312°C of T h . The laser‐Raman test shows that CO2 is found in fluid inclusions of the tungsten‐bearing quartz veins. Quadrupole mass spectrometry reveals that fluid inclusions contain major vapor‐phase contents of CO2, H2 O. Meanwhile, fluid inclusions contain major liquid‐phase contents of Cl −, Na + . It can be speculated that the ore‐forming fluid of the Xiaojiashan tungsten deposit is characterized by an H2 O–CO2, low salinity, and H2 O–CO2 –NaCl system. The range of hydrogen and oxygen isotope compositions indicated that the ore‐forming fluids of the tungsten deposit were mainly magmatic water. The ore‐forming age of the Xiaojiashan deposit should to be ~227 Ma. During the ore‐forming process, the magmatic water had separated from magmatic intrusions, and the ore‐bearing complex was taken to a portion where tungsten‐bearing ores could be mineralized. The magmatic fluid was mixed by meteoric water in the late stage. Abstract : The Xiaojiashan tungsten deposit is located about 200 km northwest of Hami City, Eastern Tianshan orogenic belt, Xinjiang, northwestern China and is a quartz vein‐type tungsten deposit. In this contribution, we report new results obtained from ore geology research, fluid inclusion and H–O stable studies for the Xiaojiashan deposit.